Organizational and technological reliability of construction in Iraq - Ahmed Abdul Ruda Awda Al-Msari; A. A. Rudenko (Вестник СибАДИ, 2023)
Introduction. The construction of capital construction facilities is a complex organizational and technological task, providing for the execution of a complex of construction and installation works, as well as organizational and technological interaction of all construction participants, including with the aim of prompt management of risks arising during construction with varying degrees of intensity and danger.Materials and methods. One of the main conditions for ensuring organizational and technological reliability in the construction industry is the full and timely provision of all types of resources, which at the current stage is not always an effectively solved scientific and practical task, due to the high level of various risks.Results. The results of the adverse consequences of the risks have a very negative and significant impact on such construction issues as compliance with the deadlines for the work, optimization of the cost of the facility at all stages of its construction, ensuring the specified quality of construction and installation. In this regard, ensuring organizational and technological reliability (OTR) of construction based on an effective resource support system, taking into account risks, is an urgent and important task.Discussion and conclusion. Consideration of the impact of construction resource supply factors is important for taking into account the risk and its consequences, as a quantitative measure to assess the negative or favorable scenario of construction progress. Assessment of various factors of resource supply will make it possible to more accurately assess the organizational and technological reliability of construction.